Experimental study on potential use of fly ash and GGBS from Jaipur plants in developing a self-compacting concrete - Sangita Rautray, Sushree; Ranjan Das, Manas (International Journal of Engineering and Technology, 2018)
Self-Compacting Concrete (SCC) is becoming a popular choice in concrete industries due to its filling ability in congested reinforcement and its auto compacting nature. In the present work, an attempt has been made to investigate the properties of fresh and hardened concrete made by partial replacement of cement by fly ash and ground granulated blast furnace slag (ggbs) in different percentages. The essential properties of freshly prepared concrete like flowability, passing ability, filling ability are determined by slump flow test, slump flow T50cm, V-funnel, J-ring and L-box test. The values are found to satisfy EFNARC guidelines. Tests have also been conducted to assess and analyze the properties of hardened concrete such as compressive strength, split tensile strength and flexural strength. Thus an attempt has been made to develop a formulation of an economically feasible and environment friendly self-compacting concrete.Â Â Â